Age and Pubertal Status-Related Changes in Reports of Perception of Personal Odors. (March 2017) - Martinec Nováková, Lenka; Plotěná, Dagmar; Havlíček, Jan
As previously suggested, preferences for kin body odor might undergo an adaptive change over the course of puberty in order to avoid potential inbreeding, resulting in aversion to body odor of the opposite-gender kin as individuals mature sexually. However, studies based on mutual body odor aversion are rather inconclusive. We therefore investigated whether children's reports of individuals smelling good or bad differed as a function of age and pubertal status. We asked 219 children (94 male) aged 10 to 15 years to assess their pubertal development using a standardized measure and to name individuals they thought smelled good or bad. Results of the present study show that the older the girls were, the more likely they were to name males than females among nice-smelling people. Further, in both girls and boys alike, children with higher puberty scores were more likely to name children than adults. Neither in girls nor in boys did we observe any concurrent effect of age or pubertal status on children's reports of persons thought to smell bad. Irrespective of whether these changes are driven by age itself or age-related phenomena, these results suggest a shift toward a more general positive attitude to peers rather than active kin avoidance.